A Web-Based Pool Facility Booking Application For UTHM Sport Centre With Device-Based Authentication - Zakaria, Jafni Hazwani; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2025)
UTHM’s pool facility relies on a manual, counter-based booking and payment system using paper records, creating three critical challenges: lack of online booking capabilities, inefficient user record management affecting emergency response, and inadequate access control. The project aims to develop a digital platform with secure authentication, online booking, and two-tier administrative access. Following a six-phase methodology, from MoSCoW-based requirements gathering to post-implementation review, the system will implement user-friendly architecture, secure coding practices, and comprehensive testing protocols. The resulting platform will benefit the stakeholder by providing secure authentication for online payments, efficient booking management, improved emergency response capabilities, and enhanced reporting tools for management decision-making, effectively transitioning the facility from paper-based to digital operations.